Pemodelan Nikel Laterit Berdasarkan Data Resistivitas Di Daerah Kabaena Selatan Kabupaten Bombana, Provinsi Sulawesi Tenggara - Santoso, Budy; Subagio, Subagio (Jurnal Geologi dan Sumberdaya Mineral, 2018)
The lateritic nickel precipitate in the South Kabaena region is found in ultramafic rocks. The lateritic nickel model in the research area is vertically comprised of overburden, limonite zone, saprolite zone, saprock zone and bedrock. The limonite zone and the saprolite zone are included in the lateritic soil and have different nickel levels. Lateritic soil has resistivity contrast to bedrock, then resistivity data can be used to model lateritic nickel precipitate.The aquisition of resistivity data using Electrical Resistivity Tomography (ERT) Method. The ERT method is a method of measuring resistivity on the ground surface by using many electrodes, in order to obtain sub-lateral and vertical resistivity distribution variations, to obtain sub-surface imagery. The electrode configuration used in data acquisition is configuration of Dipole-Dipole. The lateritic nickel precipitate is obtained by inversion modeling based on the resistivity data. Inversion modeling is done by using Res2DInv software. Based on resistivity modeling results obtained lateritic resistivity values, as follows: limonite overburden resistivity < 40 Ohm.m, limonite resistivity: (40 – 200) Ohm.m,  saprolite resistivity : (201 – 444)  Ohm.m, saprock resistivity : (246 – 645) Ohm.m and  bedrock resistivity : (645 – 3300) Ohm.mKeywords: bedrock, configuration of  Dipole-Dipole, limonite, resistivity, saprolite